Protective effects of a nanoemulsion adjuvant vaccine (2C-Staph/NE) administered intranasally against invasive Staphylococcus aureus pneumonia. Issue 18 (12th March 2018) - Yang, Liu-yang; Zhou, Heng; Yang, Yun; Tong, Ya-nan; Peng, Liu-sheng; Zhu, Bao-hang; Diao, Wei-bo; Zeng, Hao; Sun, Hong-wu; Zou, Quan-ming
Abstract : Intranasal administration with 2C-Staph/NE yielded strong mucosal response than that induced by the intramuscular vaccination route. Abstract : No licensed Staphylococcus aureus ( S. aureus ) vaccine is currently available. To develop an effective S. aureus vaccine, we selected the recombinant proteins staphylococcal enterotoxin B (rSEB) and manganese transport protein C (rMntC) as vaccine candidates and formulated a 2C-Staph vaccine. Based on the optimised formation of nanoemulsion (NE) technology, we constructed a novel NE adjuvant vaccine, 2C-Staph/NE. The 2C-Staph/NE particles showed a suitable diameter (24.9 ± 0.14 nm), a good protein structure of integrity and specificity, and high thermodynamic stability. 2C-Staph formulated with an NE adjuvant induced higher survival rates than a 2C-Staph/MF59 vaccine in sepsis and pneumonia models. Moreover, intramuscular vaccination with 2C-Staph/NE yielded protection efficacy in a sepsis model, and the intranasal vaccination route induced a potent protective effect in a pneumonia model. Intranasal vaccination with 2C-Staph/NE induced a strong mucosal response with high levels of IgA and IL-17A in bronchoalveolar lavage fluid (BALF), and the IgG levels in the BALF were comparable to those induced by the intramuscular vaccination route. Furthermore, the serum and BALF induced by intranasal administration showed potent opsonophagocytic activity against S. aureus . And, the IL-17A played a protective role in the pneumonia model demonstrated by a cytokine neutralization test. Taken together, our results showed that intranasal administration of 2C-Staph formulated with an NE adjuvant yielded ideal protection in a murine S. aureus pneumonia model.